Flow-based determination of total mercury in waters by flameless atomic absorption spectrometry - Ferreira, José Roberto; Bendassoli, José Albertino; Pessenda, Luiz Carlos Ruiz; Krug, Francisco José; Zagatto, Elias Ayres Guidetti (O Mundo da Saúde, 2024)
A flow injection analyzer is proposed for total mercury determination in natural waters by flameless atomic absorption spectrometry. Following a 30-min wet digestion with nitric acid under 90°C, in a closed Teflon vessel, a sample aliquot is inserted into an acidic carrier stream and, at the next confluence site, a 2.0% (w/v) stannous chloride solution and an argon flow are simultaneously added. After the gas/liquid phase separation, the evolved mercury vapor is directed towards a cylindrical windowless glass flow cell (16-cm optical path, 0.5-cm inner diameter). Details of the analyzer design and operation are provided. Mercury contents ≥ 0.25 ± 0.08 µg/L can be effectively determined at a sampling rate of 90/h. Good repeatability (r.s.d. ca 2.0%) was attained for 1.50 µg/L Hg, and results were in agreement with those obtained by the analogous manual procedure (t = - 0.10; P = 0.92; n = 6).